Potential methane emission reductions for two manure treatment technologies. Issue 7 (3rd April 2018) - VanderZaag, Andrew C.; Baldé, Hambaliou; Crolla, Anna; Gordon, Robert J.; Ngwabie, N. Martin; Wagner-Riddle, Claudia; Desjardins, Ray; MacDonald, J. Douglas
ABSTRACT: The effect of two dairy manure treatments, solid–liquid separation (SLS) and anaerobic digestion (AD), on methane potential and the speed of production was evaluated. Assays were performed in the lab to measure methane (CH4 ) production over 202 d from dairy manure samples taken before and after each treatment. Compared to raw manure, CH4 emissions on a per-L basis were reduced 81% by SLS and 59% by AD, on average. The mean (SD) ultimate CH4 emission potential ( B 0 ) per kg of volatile solids (VS) was 247 (8) L CH4 kg −1 VS for raw manure, 221 (9) L CH4 kg −1 VS for separated liquid, and 160 (4) L CH4 kg −1 VS for anaerobic digestate. Thus, SLS reduced the B 0 of the liquid fraction by 11% and AD reduced B 0 by up to 35% compared to raw manure. Manure treatment affected the speed of CH4 production: SLS increased the CH4 production rate and thus separated liquid manure was the fastest to produce 90% of the ultimate CH4 production. Therefore, both the speed of degradation and B 0 should be considered when assessing these techniques for farm-scale manure storages, because actual emission reductions will depend on storage conditions.